A randomised, double-blind, parallel-group study of the safety and efficacy of subcutaneous tocilizumab versus intravenous tocilizumab in combination with traditional disease-modifying antirheumatic drugs in patients with moderate to severe rheumatoid arthritis (SUMMACTA study). Issue 1 (31st July 2013) - Burmester, Gerd R; Rubbert-Roth, Andrea; Cantagrel, Alain; Hall, Stephen; Leszczynski, Piotr; Feldman, Daniel; Rangaraj, Madura J; Roane, Georgia; Ludivico, Charles; Lu, Peng; Rowell, Lucy; Bao, Min; et al.
Abstract : Objectives: This study compared the efficacy and safety of subcutaneous (SC) versus intravenous (IV) formulations of tocilizumab in patients with rheumatoid arthritis with an inadequate response to disease-modifying antirheumatic drugs (DMARD). Methods: Patients (n=1262) were randomly assigned to receive tocilizumab-SC 162 mg weekly+placebo-IV every 4 weeks or tocilizumab-IV 8 mg/kg every 4 weeks+placebo-SC weekly in combination with traditional DMARD. The primary outcome was to demonstrate the non-inferiority of tocilizumab-SC to tocilizumab-IV with regard to the proportion of patients in each group achieving an American College of Rheumatology (ACR) 20 response at week 24 using a 12% non-inferiority margin (NIM). Secondary outcomes were disease activity score using 28 joints (DAS28), ACR responses, health assessment questionnaire scores and safety assessments. Results: At week 24, 69.4% (95% CI 65.5 to 73.2) of tocilizumab-SC-treated patients versus 73.4% (95% CI 69.6 to 77.1) of tocilizumab-IV-treated patients achieved an ACR20 response (weighted difference between groups −4.0%, 95% CI −9.2 to 1.2); the 12% NIM was met. ACR50/70 responses, DAS28 and physical function improvements were comparable between the tocilizumab-SC and tocilizumab-IV groups. The safety profiles of tocilizumab-SC and tocilizumab-IV were similar, and the most common adverse event was infection. Injection-site reactions (ISR) occurred more frequently in the tocilizumab-SC group than in the tocilizumab-IV (placebo-SC) group. No anaphylaxis was reported over the 24 weeks. Conclusions: Tocilizumab-SC 162 mg weekly demonstrated comparable efficacy to tocilizumab-IV 8 mg/kg. The safety profile of tocilizumab-SC is consistent with the known and well-established safety profile of tocilizumab-IV, with the exception of a higher incidence of ISR, which were more common with tocilizumab-SC administration.